2015
DOI: 10.1037/a0037956
|View full text |Cite
|
Sign up to set email alerts
|

Does child abuse and neglect increase risk for perpetration of violence inside and outside the home?

Abstract: Objective: To examine the extent to which abused and neglected children perpetrate three different types of violence within and outside the home: criminal, child abuse, and intimate partner violence and determine whether childhood maltreatment leads to an increased risk for poly-violence perpetration. Method: Using data from a prospective cohort design study, children (ages 0-11) with documented histories of physical and sexual abuse and/or neglect (n = 676) were matched with children without such histories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 69 publications
9
96
0
1
Order By: Relevance
“…Among these factors, the exposure to DV during childhood has been one of the most prevalent predictors for DV perpetration (e.g. Capaldi et al, 2012;Carpenter & Stacks, 2009;Mbilinyi et al, 2012;Milaniak & Widom, 2015;Whitfield et al, 2003).…”
Section: Predictors Of DV Perpetrationmentioning
confidence: 99%
“…Among these factors, the exposure to DV during childhood has been one of the most prevalent predictors for DV perpetration (e.g. Capaldi et al, 2012;Carpenter & Stacks, 2009;Mbilinyi et al, 2012;Milaniak & Widom, 2015;Whitfield et al, 2003).…”
Section: Predictors Of DV Perpetrationmentioning
confidence: 99%
“…The most likely to be arrested for these crimes were children who had been physically abused. In another study of the same dataset, Milaniak and Widom () found that maltreated children, as adults, were significantly more likely than matched controls to have an arrest for violence and also to perpetrate abuse against their own children.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Wekerle et al () reported a significant association between childhood emotional abuse and later dating violence perpetration among male youth involved with child protective services. Further, Milaniak and Widom () found that adults with documented histories of child maltreatment were more likely than their matched controls to perpetrate intimate partner violence (IPV) in their late 20s.…”
Section: Introductionmentioning
confidence: 99%
“…Milaniak and Widom () found that documented cases of childhood abuse and neglect at ages 0 to 11 years predicted “poly‐violence” perpetration (criminal violence, partner assault, and child abuse) in young adulthood.…”
Section: Developmental and Psychosocial Risk Factors For Domestic Viomentioning
confidence: 99%